Interfacial engineering and thermophysical property optimization in particle-reinforced magnesium matrix composites: A theoretical modeling investigation - Li, Yunzhen; Yang, Changlin (Materials chemistry and physics, 2025)
The thermophysical properties of particle-reinforced magnesium matrix composites are the subject of considerable research interest. The incorporation of reinforcement particles has been demonstrated to exert a profound influence on the coefficient of thermal expansion (CTE) and thermal conductivity (TC) of magnesium alloy matrix. The present study is dedicated to an in-depth examination of the thermal expansion properties and thermal conductivity of particle-reinforced magnesium matrix composites. To address the limitations of conventional two-phase models, this study proposes a refined CTE prediction model that innovatively treats the stress/strain zone around particles as an independent third phase, offering a more comprehensive understanding of how internal stresses govern thermal expansion. This study aims to enhance the comprehension and forecasting of the thermal expansion behavior of composites by delving into the influence of stresses and plastic deformation zones on the thermal expansion. In terms of thermal conductivity, the introduction of reinforcement is clarified in relation to the constant pressure specific heat capacity (Cp) and density (ρ) of the magnesium matrix. Then, a multi-dimensional TC model which moves beyond idealized assumptions based on Fourier's law and thermal resistance principles is established. This model systematically incorporates the critical effects of the interfacial phase layer, including its thickness and intrinsic thermal properties, which are often overlooked. The new framework provides predictions that align more closely with experimental realities than classical models, thereby offering a more reliable tool for interfacial design and property optimization. [Display omitted] •A stress-induced third phase is proposed to model composite thermal expansion.•A 3D thermal model incorporating interfacial effects outperforms classical models.•Interfacial engineering is pivotal for tailoring thermophysical properties.